Code over country : the tragedy and corruption of Seal Team Six - Cole, Matthew (Bold Type Books, 2022)
"The Navy SEALs are, for most Americans, the ultimate heroes. Their 2011 killing of Osama Bin Laden was celebrated as a victory in the War on Terror. Former SEALs rake in thousands of dollars as leadership consultants for American corporations. And young men who want to join the military dream of serving in their elite ranks. But as recent revelations, like the uproar around former SEAL Eddie Gallagher, have shown, the SEALs have lost their bearings. Gallagher was only the tip of the iceberg. In Code Over Country, investigative journalist Matthew A. Cole tells the story of the most celebrated SEAL unit, SEAL Team 6, revealing the dark, troubling pattern of war crimes and deep moral rot hidden behind the heroic narratives. From their origins during the World War II and their first test during the Vietnam War, the SEALs were trained to be specialized killers with short missions. But as the wars in Iraq and Afghanistan turned into the endless War on Terror, their carefully-managed violence spiraled out of control. Drawing on years of reporting, Cole follows SEAL Team 6's history, the high-level decisions that unleashed their violence, and the coverups that prevented their crimes from coming to light. Code Over Country is a much-needed reckoning with the unchecked power of the military -- and the harms enacted by and upon soldiers in our name"--